2022
DOI: 10.3389/fmicb.2022.957698
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fullerenes as Photosensitizers for Antimicrobial Photodynamic Inactivation: A Review

Abstract: Antimicrobial photodynamic inactivation (aPDI) is a newly emerged treatment approach that can effectively address the issue of multidrug resistance resulting from the overuse of antibiotics. Fullerenes can be used as promising photosensitizers (PSs) for aPDI due to the advantages of high triplet state yields, good photostability, wide antibacterial spectrum, and permissibility of versatile functionalization. This review introduces the photodynamic activities of fullerenes and the up-to-date understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 120 publications
1
9
0
Order By: Relevance
“…This could be particularity related to the concentration of endogenous photosensitive substances (e.g., porphyrin and flavin derivatives), which may vary between bacterial strains of the same species. [6][7][8][9] Our results agree with other studies where aPDI/aBL therapies lead to the effective eradication of XDR Gram-negative bacteria in hospital-acquired infections, in addition to the synergistic activity that can be achieved by associating photoinactivation and clinical use of antimicrobials. 6,8,10,13 In fact, Wozniak et al 11,26 demonstrated the usefulness of the synergistic effect of different antibiotics (colistin, tetracyclines or imipenem), with sublethal doses of irradiation (63.6 J/cm 2 ) against XDR E. cloacae, K. pneumoniae and A. baumannii strains.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This could be particularity related to the concentration of endogenous photosensitive substances (e.g., porphyrin and flavin derivatives), which may vary between bacterial strains of the same species. [6][7][8][9] Our results agree with other studies where aPDI/aBL therapies lead to the effective eradication of XDR Gram-negative bacteria in hospital-acquired infections, in addition to the synergistic activity that can be achieved by associating photoinactivation and clinical use of antimicrobials. 6,8,10,13 In fact, Wozniak et al 11,26 demonstrated the usefulness of the synergistic effect of different antibiotics (colistin, tetracyclines or imipenem), with sublethal doses of irradiation (63.6 J/cm 2 ) against XDR E. cloacae, K. pneumoniae and A. baumannii strains.…”
Section: Discussionsupporting
confidence: 88%
“…Among these nanostructures are fullerenes and titanium dioxide derivatives. 9 Numerous studies agree on the potential of aBL as a therapy for the treatment of localized infections, particularly those related to skin and soft tissue infections, and also for the decontamination of surfaces, liquids, and food, thus reducing the use and exposure to antibiotics. [10][11][12][13][14] Similarly, other authors confirm that aPDI/aBL is effective in killing MDR and XDR bacteria, indicating that the use of blue light may help in containing the spread of resistance genes.…”
Section: Introductionmentioning
confidence: 99%
“…A pathological dose and duration were applied. As it is known from literature [ 25 ] and our own work [ 14c ] that fullerenol compounds can produce ROS under irradiation, together with the unambiguous proof that AcYF is present inside the cell and nowhere else, ROS generation is located inside the cell as well. Quantification using a ROS assay kit was not possible at this time.…”
Section: Resultsmentioning
confidence: 64%
“…Considering their interesting properties as an acceptor system, [2][3][4] C 60 and its derivatives are used as materials in organic solar cells [5][6][7] or to simulate photosynthetic devices. 8,9 Some derivatives are used as liquid crystals 10 and in medicine as anticancer, [11][12][13] antimicrobial, [14][15][16][17] antiviral agents against HIV 18 and recently anti-SARS-CoV 2, 19,20 as well as potential therapeutic agents for neurodegenerative disorders. 21 In Alzheimer's disease, C 60 derivatives have shown capacity to interfere with the amyloid β-peptide fibril formation.…”
Section: Introductionmentioning
confidence: 99%